Trends in interracial unions in Brazil between 2002 and 2022: anything new? - Maria Carolina Tomás (Revista Brasileira de Estudos de População)
Abstract Using data from the Pesquisa Nacional por Amostra de Domicílios for the years 2002, 2007, 2012, 2017, and 2022, this study analyzes the overall patterns of interracial unions in Brazil, considering regional differences and educational distance between partners. The objective is to analyze whether patterns of interracial unions have changed or remained consistent in a context of significant changes in racial relations, including the valorization of Black culture and the implementation of affirmative action policies. The findings indicate a stabilization in these rates during this period (about 30%) with no evidence of an increasing trend. However, important differences emerge when considering specific racial combinations, such as a rise in brown and black homogamy rates. Regional differences highlight the impact of local racial distribution and local specificities of racial classification and racial tolerance. Additionally, the data also provide evidence supporting the status exchange hypothesis, where the darker-skinned partner tends to have a higher educational level. However, this finding may not necessarily indicate an intentional trade but rather reflect how marital preferences operate and has been changing. These results are preliminary and descriptive, intended to generate hypotheses and underscore the need for further research on this topic.